Trans-cend health the transcendence of a medical support and wellness facility for the LGBTQIA+ community - Gandingco, Ma. Jacqueline C.
People experience the built environment differently. A quick trip to a healthcare or public facility can have a positive or negative impact on a person. There has been a long history of discrimination of the lesbian, gay, bisexual, transgender, queer, intersex, and asexual+ (LGBTQIA+) persons from healthcare providers or strangers in healthcare facilities. Moreover, gender-specific public facilities such as changing rooms, restrooms, or shower rooms lack privacy or inclusivity to persons with disabilities, transitioning, non-binary, or those who require special assistance. The study aims to raise awareness and highlight the importance of LGBTQIA+ health and well-being and offer specific services to the transgender and non-binary persons, and provide concrete and tangible solutions to a more inclusive environment, such as: safe spaces, health and wellness care, facilities, and environment. This study looks into the possibility of building an LGBTQIA+ medical support and wellness facility along Sumulong Highway, Barangay Sta. Cruz, Antipolo City. The proposed facility will hopefully propel the transcendence of architecture as a way to alleviate some of the stresses LGBTQIA+ persons encounter at the current healthcare facilities we have in the country and create a pleasant experience for all that focuses on inclusivity, sustainability, and safety.